Outlaw girls escape from prison: Gender, resistance and playfulness - Emmerich, Fabienne (Punishment & society, 2020)
Prison resistance practices are increasingly understood as gendered and linked to subjectivation. This article builds on this growing body of knowledge, but with a different and largely under explored focus, namely the confrontational resistance practices of women political prisoners. The objective is to explore how gendered resistance practices disrupt dominant constructions of gender through the lens of the hidden preparations and implementation of a historical women’s escape. This is done through a gendered analysis of narrative and auto/biographical material of a 1976 prison break in Germany, in which four women of the Red Army Faction (RAF) and June 2nd Movement (J2M) escaped from the women’s prison in West Berlin. Drawing on the works of poststructuralist feminists, the article expands our theoretical understanding of resistance to include the recognition of playfulness and laughter in the processes of subjectivation. It argues that opening up gendered resistance practices to play and laughter, lets us see the women’s escape as a subversive reversal of the heroic, masculine prison break, in which their subjectivity as revolutionary violent women is revealed.